The effect of yeast-derived β-glucans in reducing the adverse outcome of Lawsonia intracellularis in finishing pigs - Rhayat, Lamya; Even, Gaël; Kiros, Tadele G.; Kuhn, Géraldine; Lebrun-Ruer, Ségolène; Audebert, Christophe; Schulthess, Julie (Frontiers in Animal Science, 2023)
Chronic diarrhoea is one of the most recurrent health issues in pig herds. Among the causative agents of diarrhoea, Lawsonia intracellularis is quite frequent with worldwide distribution leading to detrimental economical losses, as a result of the poor growth rate of the infected pigs. A growing body of evidence has shown that branched yeast β-glucans are excellent inducers of innate immunity memory in humans and in pigs. In this study, yeast branched β-glucans were evaluated as a potential solution to control infection by L. intracellularis in pigs by reducing the shedding of L. intracellularis in the faeces of infected animals. To address this hypothesis, naturally infected grow finishing pigs were divided into two treatment groups (n=80) and fed either with a basal diet (Control) or the same basal diet supplemented with 250 g/ton β-glucans (BG-fed group). Our results have shown that BG-supplemented pigs during the growing and finishing period had significantly increased body weight (BW) by 4.22 kg on average on day 97 and ADG up to 5.6% over the whole experiment (p<5.0 x 10 -2 0.05) with no significant increase in ADFI. Similarly, supplementation of pigs with BG during the grow-finish phase has significantly reduced (p<4.0x10 -4 0.0004) faecal shedding of the bacteria in infected pigs on day 97. Furthermore, our results indicate that microbial α-diversity was negatively correlated with the presence of L. intracellularis. Animals fed with yeast BG show a reduction of the two genera Sarcina and Catenibacterium and a deeper analysis indicated that the ratio of Fibrobacter to Lacnospiraceae_AC2044 group could be a potential marker for L. intracellularis susceptibility. This study demonstrated the beneficial effect of adding branched yeast BG in the diet of grow-finish pigs in reducing the dissemination of L. intracellularis between pigs in a given herd.